2005
DOI: 10.1115/1.1824103
|View full text |Cite
|
Sign up to set email alerts
|

The Tracking of the Sun for Solar Paraboloidal Dish Concentrators

Abstract: Paraboloidal dish concentrators need tracking the sun in the east-west and north-south direction continuously throughout the year. But this paper explains the method of intermittent tracking of the sun in the north-south direction with no tracking in the east-west direction for less energy yield. The frequency of tracking in the north-south direction is determined by the relationship between the variation in solar altitude angle and the size of the absorber in the Paraboloidal dish concentrator. A computer pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 3 publications
0
10
0
Order By: Relevance
“…The effects of tracking errors on the performance of the point focus system were analysed by Hughes . The method of one‐axis tracking of the sun in the north to south direction is explained for parabolic dish concentrator (PDC) by Shanmugam and Christraj . The effect of continuous operation of a low‐cost electromechanical two‐axis tracking system on the solar energy collected in a parabolic trough collector system was investigated by Bakos, and it was observed that there was a 46.46% increase in the collected solar energy compared with fixed surface.…”
Section: Introductionmentioning
confidence: 99%
“…The effects of tracking errors on the performance of the point focus system were analysed by Hughes . The method of one‐axis tracking of the sun in the north to south direction is explained for parabolic dish concentrator (PDC) by Shanmugam and Christraj . The effect of continuous operation of a low‐cost electromechanical two‐axis tracking system on the solar energy collected in a parabolic trough collector system was investigated by Bakos, and it was observed that there was a 46.46% increase in the collected solar energy compared with fixed surface.…”
Section: Introductionmentioning
confidence: 99%
“…A programmable logic controller (PLC) was used to calculate the solar vector and to control the sun tracker so that it follows the sun's trajectory. In addition, Shanmugam & Christraj (2005) presented a computer program written in Visual Basic that is capable of determining the sun's position and thus drive a paraboloidal dish concentrator (PDS) along the East-West axis or North-South axis for receiving maximum solar radiation. In general, both sun-tracking approaches mentioned above have both strengths and drawbacks, so some hybrid sun-tracking systems have been developed to include both the open-loop and closed-loop sensors for the sake of high tracking accuracy.…”
Section: Introductionmentioning
confidence: 99%
“…The solar energy absorbed by these collectors can be increased by their integration with solar tracking systems which compute the direction of the solar vector based on location and time [1]. Using such tracking systems, the effectiveness of the solar collectors can be enhanced by ensuring that they are always oriented toward the sun [2][3][4][5][6][7][8][9][10][11][12][13] Solar orientation measurement is an essential task in the solar energy field. Many previous studies have addressed the application of solar collectors in the development of solar energy technologies [14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%